A synthesis of methane emissions from 71 northern, temperate, and subtropical wetlands. (28th April 2014) - Turetsky, Merritt R.; Kotowska, Agnieszka; Bubier, Jill; Dise, Nancy B.; Crill, Patrick; Hornibrook, Ed R. C.; Minkkinen, Kari; Moore, Tim R.; Myers‐Smith, Isla H.; Nykänen, Hannu; Olefeldt, David; Rinne, Janne; et al.
Abstract Wetlands are the largest natural source of atmospheric methane. Here, we assess controls on methane flux using a database of approximately 19 000 instantaneous measurements from 71 wetland sites located across subtropical, temperate, and northern high latitude regions. Our analyses confirm general controls on wetland methane emissions from soil temperature, water table, and vegetation, but also show that these relationships are modified depending on wetland type (bog, fen, or swamp), region (subarctic to temperate), and disturbance. Fen methane flux was more sensitive to vegetation and less sensitive to temperature than bog or swamp fluxes. The optimal water table for methane flux was consistently below the peat surface in bogs, close to the peat surface in poor fens, and above the peat surface in rich fens. However, the largest flux in bogs occurred when dry 30‐day averaged antecedent conditions were followed by wet conditions, while in fens and swamps, the largest flux occurred when both 30‐day averaged antecedent and current conditions were wet. Drained wetlands exhibited distinct characteristics, e.g. the absence of large flux following wet and warm conditions, suggesting that the same functional relationships between methane flux and environmental conditions cannot be used across pristine and disturbed wetlands. Together, our results suggest that water table and temperature are dominant controls on methane flux in pristine bogs and swamps, while other processes, such as vascular transport in pristine fens, have the potential to partially override the effect of these controls in other wetland types. Because wetland types vary in methane emissions and have distinct controls, these ecosystems need to be considered separately to yield reliable estimates of global wetland methane release.